2019
DOI: 10.1080/13670050.2019.1671308
|View full text |Cite
|
Sign up to set email alerts
|

Does CLIL shape language attitudes and motivation? Interactions with target languages and instruction levels

Abstract: Besides being promoted as a way to improve target language proficiency, Content and Language Integrated Learning (CLIL) is also believed to positively impact socio-affective variables such as language attitudes and motivation (European Commission, 2014). Yet, few extensive empirical studies exist on these aspects in CLIL. The present contribution aims to address this gap in the literature by investigating language attitudes and motivation in CLIL on a large scale across two target languages (English and Dutch)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 51 publications
4
19
0
4
Order By: Relevance
“…The researchers found significantly higher levels of FLE and lower levels of FLCA for English than for Dutch, a language associated with the Flemish community with whom Belgian Francophones have a tense relationship and a language perceived as less useful than English despite the fact that Dutch is often required for jobs in Belgium. A follow-up study by the same authors showed similar patterns for language attitudes and motivation, with significantly more positive attitudes towards the target languages in the CLIL schools compared to the non-CLIL schools and higher perceived attractiveness and easiness of English compared to Dutch at the start of secondary education (De Smet et al, 2019).…”
Section: The Role Of the Specificity Of The Fl And The Meso-and Macromentioning
confidence: 72%
See 1 more Smart Citation
“…The researchers found significantly higher levels of FLE and lower levels of FLCA for English than for Dutch, a language associated with the Flemish community with whom Belgian Francophones have a tense relationship and a language perceived as less useful than English despite the fact that Dutch is often required for jobs in Belgium. A follow-up study by the same authors showed similar patterns for language attitudes and motivation, with significantly more positive attitudes towards the target languages in the CLIL schools compared to the non-CLIL schools and higher perceived attractiveness and easiness of English compared to Dutch at the start of secondary education (De Smet et al, 2019).…”
Section: The Role Of the Specificity Of The Fl And The Meso-and Macromentioning
confidence: 72%
“…Secondly, SLA researchers have typically focused on phenomena in a single FL (most often English) with the assumption that they applied to all FLs. Following research that has examined anxiety in two FLs (Dewaele, 2002;Rodríguez & Abreu, 2003;Santos et al, 2017), enjoyment and anxiety in two FLs (De Smet et al, 2018;Dewaele & Proietti Ergün, to appear;Resnik & Dewaele, 2020) and comparisons of levels of motivation and attitudes in two FLs that were official school languages (De Smet et al, 2019), we seek to investigate to what extent classroom emotions and attitudes/motivation are language-specific and to what degree the relationships between emotional, attitudinal/motivational and performance variables are similar in learners' different FLs.…”
Section: Introductionmentioning
confidence: 99%
“…4) que a continuación se muestran, podremos observar cómo los participantes de colegios AICLE obtienen mejores resultados que sus compañeros de colegios que no utilizan la metodología AICLE en los factores de motivación extrínseca, motivación intrínseca y los yoes. Ello parece indicar que los resultados alcanzados tras evaluar a los niños de enseñanza primaria en el CRIEC están en armonía con los obtenidos por De Smet et al (2019), Doiz et al (2014), Fernández-Fontecha y Canga Alsonso (2014), Lasagabaster (2011), Lasagabaster y Sierra ( 2009) y Seikkula-Leino ( 2007), quienes demostraron que los estudiantes de primaria y secundaria que formaban parte de programas AICLE en Europa estaban más motivados que sus compañeros que no estaban inmersos en estos programas. Resulta notable el caso de los estudios llevados a cabo en el contexto vasco, un contexto especialmente interesante para los estudios sobre bilingüismo, puesto que en esta comunidad se favorece el multilingüismo desde las instituciones.…”
Section: Análisis Y Resultadosunclassified
“…Todos estos estudios comparten el hecho de que el inglés es la lengua vehicular que se utiliza en AICLE, bien sea en España (País Vasco, La Rioja o Cataluña) o en Europa (Bélgica o Finlandia). Otros rasgos que comparten todas las investigaciones llevadas a cabo sobre motivación es que la metodología empleada es de corte cuantitativo, son estudios longitudinales y los instrumentos administrados para alcanzar resultados son esencialmente cuestionarios (De Smet et al, 2019;Doiz et al, 2014;Pladevall-Ballester, 2019). La mayoría de ellos tienen en común que todos analizan la repercusión de la motivación en el aprendizaje de una segunda lengua o de lengua extranjera en la etapa de educación secundaria, excepto el estudio de Fernández-Fontecha y Canga Alonso (2014), quienes en la Rioja descubrieron que los alumnos de educación primaria que formaban parte del programa AICLE estaban más motivados que sus compañeros.…”
Section: La Relación Entre Educación Bilingüe Y Las Variables Afectivasunclassified
See 1 more Smart Citation